Effects of Ag, ZnO and TiO2 nanoparticles at low contents on the crystallization, semicrystalline morphology, interfacial phenomena and segmental dynamics of PLA. (June 2021) - Črešnar, Klementina Pušnik; Zemljič, Lidija Fras; Papadopoulos, Lazaros; Terzopoulou, Zoi; Zamboulis, Alexandra; Klonos, Panagiotis A.; Bikiaris, Dimitrios N.; Kyritsis, Apostolos; Pissis, Polycarpos
Graphical abstract: Highlights: PLLA reinforced with Ag, ZnO and small TiO2 nanoparticles: synthesis and investigation. Interfacial interactions resulted in formation of rigid amorphous fraction (RAF). The nanoparticles favor faster crystallization; however, not acting as additional nuclei. Severely altered semicrystalline morphology, with larger spherulites in the nanocomposites. Accelerated chains diffusion in the composites and indications for changes in free volume. Abstract: Polymer nanocomposites, PNCs, based on polylactide (PLA, molar mass 75 kg/mol) reinforced with metal and metal oxide nanoparticles, commercial silver (Ag, ∼10 nm in size), zinc oxide (ZnO, <10 nm) and titania (TiO2, 3−5 nm), at small fractions (0.5, 1 and 2.5 wt%), are comparatively studied here. The main scope is the evaluation of the direct and indirect effects of the fillers on the in general slow crystallization rate of PLA, the latter being wanted in processing of this widely used renewable polymer. In addition, we explore the impact of the polymer-filler interactions on polymer mobility in connection to crystallizability. The following sum of complementary techniques are employed, attenuated total reflection Fourier transform infra red spectroscopy, X-ray diffraction (XRD) spectroscopy, differential scanning calorimetry (DSC), polarized optical microscopy (POM) and dielectric relaxation spectroscopy (DRS). Opposite to most cases of PLA-based PNCs, the fillers do not act as nuclei here and their role is indirect. The polymer seems to interact with the fillers resulting in the formation of an interfacial rigid amorphous fraction. Due to the presence of fillers surrounded by bound PLA, there seems to be an acceleration of the bulk-like chains diffusion ( T g slightly drops), most probably due to free volume increase. Subsequently, the easier chains diffusion leads free volume holes (defects) toward the polymer/nanoparticle interfaces, based on previously proposed model [Polymer 53 (2012) 1362–1372]. This leads to, in general, faster hot crystallization rate and thicker crystal lamellae (XRD). In the PNCs, quite larger however fewer spherulites formed in the PNCs as monitored by POM. DRS enabled the recording of segmental dynamics, which exhibits faster time scale and weakly improved cooperativity. Next to that, an additional molecular dynamics process was revealed to possibly arise from the polymer located around the nanoparticles. Finally, the overall data demonstrate the possibility to tune semicrystalline morphology and, indirectly, the mechanical performance and the diffusion of small molecules over the PNC volume, which is wanted in both applications and processing.